MOLECULARLY IMPRINTED POLYMERS FOR CONTROLLING DRUG RELEASE. PART 1: SYNTHESIS AND CHARACTERIZATION. - Margarita Domingues Sousa (2009)
MOLECULARLY IMPRINTED POLYMERS FOR CONTROLLING DRUG RELEASE. PART 1: SYNTHESIS AND CHARACTERIZATION. Molecularly imprinted polymers (MIPs) consist of synthetic macromolecular matrix, obtained through molecular imprinting-based methods that show ability to selectively recognize important biological molecules and its application in the drug delivery field is under development. In the present review the main aspects related to the synthesis and characterization of MIPs are studied. The fundamental variables participating in the synthesis process. Such as template molecule, functional monomers. cross-linking agents, solvents, and imprinting approaches are discussed, Moreover. the main available methods for MIPs chemical and morphological characterization are presented and the importance of the obtained information is discussed.